A presença da angústia em um conto de Mia Couto - Biziak, Jacob dos Santos [UNESP]; Gobbi, Marcia Valeria Zamboni [UNESP] (My University, 2014)
This article intends an approach among literary analysis, philosophy and psichoanalysis in a short story from Mia Couto, Mozambican author. From the trajectory of the main character and from their relationship with the others, we intended to do a reading on the presence of anguish within this literary text. In order to do that, two definitions were used to explain what would be considered torment: one from the philosopher Kierkegaard and the other from the psichoanalyst Freud. Concluding, we aim to compare this two readings in a way that we establish bounds between both.

Este artigo pretende fazer uma aproximação entre a análise literária, a filosofia e a psicanálise em um conto de Mia Couto, autor moçambicano. A partir do percurso da personagem central e do seu relacionamento com as demais, procuramos fazer uma leitura sobre a presença da angústia dentro desse texto literário. Para tanto, utilizamos duas definições para o que seria a angústia: a do filósofo Kierkegaard e a do psicanalista Freud. Por fim, pretendemos comparar essas duas leituras de forma a estabelecer vínculos entre ambas.
Keywords: Anguish; Kierkegaard; Freud; Mozambican literature; Mia Couto; Angústia; Kierkegaard; Freud; Literatura moçambicana; Mia Couto